2020
DOI: 10.3389/fmed.2020.00418
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients at Risk for Recurrent Disease Activity After Switching From Remicade® to Remsima®? An Observational Study

Abstract: Background: Since the late '90s, infliximab (Remicade ®) is being used successfully to treat patients with several non-infectious immune mediated inflammatory diseases (IMIDs). In recent years, infliximab biosimilars, including Remsima ® were introduced in clinical practice. Aim: To investigate the interchangeability of Remicade ® (originator infliximab) and its biosimilar Remsima ® in patients with rare immune-mediated inflammatory diseases (IMIDs). Methods: This two-phased prospective open label observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…However, the study did report therapy failure or exacerbation of neurological symptoms in a substantial number of patients who were diagnosed with granuloma, including (neuro)sarcoidosis. In contrast to Xue et al, we did not observe a large number of patients to have treatment failure/exacerbation during our 6 months versus their 2 years [ 25 ] follow-up.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the study did report therapy failure or exacerbation of neurological symptoms in a substantial number of patients who were diagnosed with granuloma, including (neuro)sarcoidosis. In contrast to Xue et al, we did not observe a large number of patients to have treatment failure/exacerbation during our 6 months versus their 2 years [ 25 ] follow-up.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, there was no relapse observed in seven neurosarcoidosis patients during the 6 months follow-up. In addition, Xue et al conducted a prospective observational monitoring study of 48 rare immune-mediated inflammatory diseases patients (among which 17 with sarcoidosis) that were switched from Remicade ® to Remsima ® [ 25 ]. No significant differences were observed for patient-reported outcomes, physician perception disease activity, and laboratory parameters after switching from Remicade ® to Remsima ® .…”
Section: Discussionmentioning
confidence: 99%
“…However, this study included only eight patients, all diagnosed with neurosarcoidosis. Xue et al [ 33 ] also reported failure of infliximab biosimilar in patients with neurosarcoidosis, with effect regained after retransitioning. The authors attributed this finding to variations in afucosylation between the originator and biosimilars, which might be associated with differences in biological activity specifically in sarcoidosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies concluded that there were no major safety issues, including immunogenicity, after transitioning [14]. However, some studies have shown that patients who transitioned to a biosimilar experienced loss of effect and/ or adverse events (AEs), resulting in higher discontinuation rates than in patients who remained on the originator [15][16][17][18]. It has also been shown that, of all patients who transitioned from originator to biosimilar, 2.6-25.8% restarted treatment with the originator (retransitioning) [16,19].…”
Section: Key Pointsmentioning
confidence: 99%
“…Recently, biosimilars are also used in BD patients. Although a first study has shown a loss of efficacy in 3 patients after switch to an IFX biosimilar, subsequent studies reported good efficacy and safety profile of IFX biosimilar after a start or switch from the originator [11][12][13][14].…”
Section: Biologic Treatmentsmentioning
confidence: 99%